Inguinal Hernia: A Probable Complication of Urinary Schistosomiasis in School Age Male Children in an Area Highly Endemic for Schistosoma Haematobium in Zambia. - Mwanakasale, Victor; Tente, Catherine; Chungu, Joseph; Xu, Jing; Zhou, Xiao-nong (Journal of Preventive Medicine And Care, 2017)
Introduction Schistosoma haematobium infection is acquired early in life with the peak prevalence and intensity of infection occurring in the second decade of life in endemic areas. The aim of this study was to establish any association between S. haematobium infection and development of inguinal hernia in school age children in a S. haematobium highly endemic area in Zambia. Methodology An analytical study was conducted at St Paul’s Mission Hospital, Nchelenge, Luapula province, Zambia. Hospital operating theatre records were reviewed for inguinal hernia repair operations in school age children. Results There were 45 inguinal hernia repair operations conducted in male school age children presumed to be infected with S. haematobium between July 2010 and July 2015. The mean age of these children was 9.6 years while the age range was from 6 years to 14 years. The overall prevalence of S. haematobium in school age children in the area ranged from 89.5% to 95.5% during this period. Conclusion Inguinal hernia is a probable complication of S. haematobium infection in school age male children.
Keywords: Schistosoma haematobium; Inguinal hernia; children.